231k views
0 votes
Solve for n: -4(3n+3)=5(-2-6n)-2

User Farrad
by
5.3k points

1 Answer

2 votes

Answer:

n=0

Explanation:

We want to solve for n in the equation

-4(3n+3)=5(-2-6n)-2

We expand using the distributive property to obtain:

-12n-12=-10-30n-2

We group similar terms to get:

-12n+30n=-10+12-2

We simplify to get:

18n=0

Divide through by 18 to get:

n=0

User Dileep Patel
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.